Sodium-glucose cotransporter 2 inhibitors in patients with type 2 diabetes and myocardial infarction undergoing percutaneous coronary intervention: A systematic review and meta-analysis - Huzaifa Ul Haq Ansari; Muhammad Ammar Samad; Eman Mahboob; Eeshal Zulfiqar; Shurjeel Uddin Qazi; Areeba Ahsan; Mushood Ahmed; Faizan Ahmed; Raheel Ahmed; Shafaqat Ali; Mahboob Alam; Jamal S. Rana; et al. (American Journal of Preventive Cardiology)
Background: Sodium-glucose cotransporter 2 inhibitors (SGLT2i) have shown benefits in improving cardiovascular (CV) outcomes in patients with heart failure (HF) and may mitigate symptom progression in myocardial infarction (MI). However, their effectiveness in patients with type 2 diabetes and MI undergoing percutaneous coronary intervention (PCI) is unclear. Methods: To identify eligible studies, a comprehensive search of electronic databases, PubMed, Cochrane Library, Scopus and Embase, was conducted from inception until May 2024. Results were presented as risk ratios (RR) and their corresponding 95 % confidence intervals (CIs). Results: Our analysis included 8 observational studies comprising 24,229 patients. The results indicated that SGLT2i with PCI was associated with a significantly reduced risk of all-cause death (RR=0.61; 95 % CI=0.54 to 0.68), CV death (RR=0.46; 95 % CI=0.22 to 0.94), major adverse cardiovascular events (RR=0.80;95 % CI: 0.66 to 0.96), HF-related hospitalizations (RR=0.63; 95 % CI=0.44 to 0.90), stroke (RR=0.77; 95 % CI: 0.62 to 0.96) and acute kidney injury (RR=0.46; 95 % CI: 0.25 to 0.84) compared to PCI without SGLT2i use. However, the risk of revascularization remained comparable between the groups. Conclusion: Our study demonstrates that SGLT2i with PCI in patients with type 2 diabetes and MI are associated with improved CV outcomes compared to PCI without SGLT2i use. Randomized controlled trials are required to confirm the improvement in outcomes with SGLT2i therapy combined with PCI in patients with MI and diabetes.